Memória dos verdes anos: saudade da infância na música popular brasileira - uma investigação e uma proposta de análise de dados - Nascimento, Adriano Roberto Afonso do (2004)
Despite the current interest of Humanities in the Memory question, the recurrence in which recorded events are identified as nostalgic in day to day discourse of Brazilians has been underestimated. Memory and Nostalgia (here understood as missing or longing after a lost past, after the Portuguese word ´Saudade´) do not have the same meaning, but are strongly related. As it points out to an affective component of the mnemonic content, the problems of this relation are of interest for the understanding of ampler psychosocial processes. Considering that constitutive elements of Social Memory are shared, it is possible to perceive the quotidian meaning of Nostalgia, what is investigated through the identification of elements commonly characterized as nostalgic, as well as the relation between these elements, and their constancies and inconstancies, in textual material about childhood nostalgia. The “boyhood times” are recurrently identified as nostalgic both in the artistic-cultural productions and in the common man memories, what justifies the choice of this particular remembrance as valid. Since the amount and the variety of elements which potentially could be remembered nostalgically were large, we opted for the conjugation of different procedures to analyze these memories. The source of nostalgic reports about childhood was a set of popular song lyrics of our country, documental material that has been progressively valued in historical-cultural studies for its characteristics of, among other advantages, picturing elements of the daily life of both the song writers and the consumer public. With the objective of evaluating the vocabulary and the nostalgic content made explicit in the lyrics of 70 (seventy) songs of Brazilian popular music, they were submitted to a software for statistical analysis of textual data (Alceste) and to a classical procedure of Content Analysis. A complementary procedure, which was called Content Networks, was proposed in order to evaluate the characteristics of the links between the elements remembered by the song writers. The results show a high frequency of mentions of child activities, child plays and games, predominantly realized outside the domestic space. The sociability network, which groups other boys, the family and young love, was also well cited. The possible localization of the physical space where the childhood occurred, indicated through the mention of natural elements, suggests the constant presence of memories of a childhood lived in the country, in opposition of an adulthood lived in urban areas. The integrated treatment of the utilized analyses procedures’ results permitted the characterization of the dynamics of the nostalgic discourse as agreeing with the more general dynamics of Social Memory. In special, the explicit identification of value for the memories indicate a particularity of this discourse, since it aggregates a sentimental value which avoids it to be taken as a mere description of the past. In this sense, the analyzed lyrics set takes us to the perception of aspects of the present of who remembers. In the comparison of a happy past and a not so happy present, the coherence of the discourse of who remembers the childhood nostalgically is in play.